Hubungan Indeks def-t Karies Gigi dengan Status Gizi pada Anak Usia 6-9 Tahun di SDN 003 Sungai Kunjang Samarinda: The Correlation between the def-t Dental Caries Index and the Nutritional Status of Children Aged 6-9 Years in State Elementary School (SDN) 003 Sungai Kunjang Samarinda - Putra, Muhammad Fikri Fadhilah; Cahya, Wahyuni Dwi; Kuntari, Indriana Dwi (Jurnal Sains dan Kesehatan, 2025)
Children in the school-age group are in the process of transitioning from childhood to adolescence. The period of childhood is crucial for establishing a strong basis for the development of high-quality individuals, and oral health plays a significant role in determining the quality of human resources. Dental caries is a frequently encountered issue in teeth and oral health. Childhood dental caries can result in discomfort, impairing the ability to chew (mastication), impacting food consumption, and contributing to inadequate nutritional health. The objective of this study is to establish the correlation between the def-t dental caries index and the nutritional status of children aged 6-9 years in SDN 003 Sungai Kunjang, Samarinda City. This study is a cross-sectional research conducted on a group of 163 students. The data underwent processing and analysis through the utilization of the Chi-Square test. The findings indicated that the prevalence of dental caries among children aged 6-9 years in SDN 003 Sungai Kunjang was relatively low (43.5%). Additionally, the most prevalent category of nutritional status was found to be normal, accounting for 49.6% of the sample. The correlation between dental caries and nutritional status was found to be statistically insignificant, with a p-value of 0.802 (p > 0.05). The study reveals no significant correlation between the def-t dental caries index and nutritional status among children aged 6-9 years in SDN 003 Sungai Kunjang, Samarinda City. Keywords:          Dental caries, nutritional status, young individuals   Abstrak Anak sekolah merupakan usia peralihan dari anak-anak menjadi remaja. Anak usia sekolah merupakan masa untuk meletakkan landasan kokoh bagi terwujudnya manusia yang berkualitas dan kesehatan rongga mulut merupakan faktor penting yang menentukan kualitas sumber daya manusia. Permasalahan yang umum terjadi pada gigi dan mulut adalah karies gigi. Karies gigi yang terjadi pada anak akan menyebabkan munculnya rasa sakit sehingga menyebabkan terganggunya fungsi pengunyahan (mastikasi) yang mempengaruhi asupan makan dan membuat status gizi menjadi buruk. Tujuan penelitian ini untuk mengetahui hubungan indeks def-t karies gigi dengan status gizi pada anak usia 6-9 tahun di SD Negeri 003 Sungai Kunjang Kota Samarinda. Penelitian ini merupakan penelitian dengan pemilihan desain cross sectional dengan banyak sampel 163 siswa. Data diolah dan dianalisis dengan uji Chi-Square. Hasil penelitian menunjukkan distribusi karies terbanyak pada anak usia 6-9 tahun di SDN 003 Sungai Kunjang adalah rendah (43,5%) dan distribusi kategori status gizi terbanyak adalah normal (49,6%). Korelasi karies gigi dengan status gizi menunjukkan p = 0,802 (p > 0,05). Disimpulkan bahwa tidak terdapat korelasi yang bermakna antara indeks def-t karies gigi dengan status gizi pada anak usia 6-9 tahun di SD Negeri 003 Sungai Kunjang Kota Samarinda. Kata Kunci:         Karies gigi, status gizi, anak